The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajpheart.00774.2015
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the molecular structure of the blood-brain barrier in the cerebral cortex and white matter: an in silico, in vitro, and ex vivo study

Abstract: The blood-brain barrier (BBB) is the main interface controlling molecular and cellular traffic between the central nervous system (CNS) and the periphery. It consists of cerebral endothelial cells (CECs) interconnected by continuous tight junctions, and closely associated pericytes and astrocytes. Different parts of the CNS have diverse functions and structures and may be subject of different pathologies, in which the BBB is actively involved. It is largely unknown, however, what are the cellular and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 47 publications
(55 reference statements)
3
44
0
5
Order By: Relevance
“…Thus, the dynamics of astrocyte proliferation are similar across regions, but the extent of their proliferation is initially lower in the WM. Indeed, access to vascular‐derived signals that are important for GM astrocyte proliferation (Bardehle et al, ; Sirko et al, ) might be less accessible for WM astrocytes given the lower vessel density in the WM in mice and human patients (Ballabh, Braun, & Nedergaard, ; Cavaglia et al, ; Joutel & Chabriat, ; Nyúl‐Tóth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the dynamics of astrocyte proliferation are similar across regions, but the extent of their proliferation is initially lower in the WM. Indeed, access to vascular‐derived signals that are important for GM astrocyte proliferation (Bardehle et al, ; Sirko et al, ) might be less accessible for WM astrocytes given the lower vessel density in the WM in mice and human patients (Ballabh, Braun, & Nedergaard, ; Cavaglia et al, ; Joutel & Chabriat, ; Nyúl‐Tóth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the results demonstrated that although TGs could significantly increase the expressions of ZO-1, claudin-5, and occludin proteins in MCAO-induced brain tissues, neither PSs nor OSs did. The BBB consists of cerebral endothelial cells and is closely associated with pericytes (Nyul-Toth et al, 2016). Pericytes are vital to BBB integrity (Bell et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, NGF is not able to pass the BBB which effectively controls the cellular and molecular traffic between the brain and the periphery [8,44]. To bypass this barrier, previous studies utilized infusion into cerebral ventricles leading to a significant…”
Section: Discussionmentioning
confidence: 99%